Psychological Diagnostics of Developmental Disorders: A New Concept - Lubovsky V.I; Korobeynikov I.A; Valyavko S.M (Moscow State University of Psychology and Education, 2017)
The authors propose a fundamentally new, theoretically grounded and empirically supported approach to psycho-pedagogical diagnostics of developmental disorders. It is shown that in Russia psychological diagnostics of developmental disorders still has no proper theoretical foundations and is carried out rather intuitively and empirically, even on the stage of differential diagnosis. The situation abroad is quite similar despite the use of standardized intelligence tests as they can only measure quantitative differences in subjects' performance. The authors emphasize core components of cognitive activity different correlation of which determines the differences between various types of intellectual disorders that are similar in presentation. The proposed approach allows us to fully use the relevant characteristics of different types of developmental disorders. Features of the dynamics of cognitive activity, which are identified in observations and ignored in testing, significantly complement the psychological characteristics of developmental disorders.